Concurrent Utero-Vaginal Prolapse with Cervical Angiomyofibroblastoma: A Rare Disease with Distinct Entity - Lee, CL; Ng, BK; Nurismah MI,; Chew, KT; Aruku N,; Lim, PS (Faculty of Medicine, UKM Medical Centre, 2015)
We report the case of a rare, benign mesenchymal tumour arising from the cervix. A 53-year-old post-menopausal woman presented with mass per vagina. Examination revealed stage 2 utero-vaginal prolapse and multiple elongated polyps seen at the cervix. She underwent local excision. Histopathological examination findings and the immunohistochemical studies were consistent with Angiomyofibroblastoma.